Modulation of ROS/NO production by murine peritoneal macrophages in response to bacterial CPG DNA stimulation - Olishevsky, S.; Burlaka, Burlaka A.P.; Sidorik, E.; Shlyakhovenko, V.A.; Garpenko, Yu.; Kozak, V. (Experimental Oncology, 2006)
Aim: To investigate the features of metabolic activation induced by bacterial CpG DNA (bCpG DNA) in peritoneal macrophages (PMjs). Methods: Electron paramagnetic resonance spin-trapping technique using respective spin traps was applied to study the generation rate of reactive oxygen species and NO production by PMjs of BALB/c mice. Results: For the first time the capability of bCpG DNA isolated from Bacillus subtilis GP1-807-03 culture medium to elevate activity of NADP·H oxidase and inducible NO synthase in PMjs of normal and tumor-bearing mice have been demonstrated. The main differences in superoxide anion generation rate and production of NO by PMjs of normal mice and mice with transplanted solid Ehrlich carcinoma were showed. The effects of bCpG DNA stimulation in vitro on ROS and NO production by PMjs depended on concentration and time exposure with bCpG DNA. Furthermore, response of PMjs from tumor-bearing mice on bCpG DNA stimulation was delayed as compared to PMjs of normal mice. Conclusion: The present findings suggest that bCpG DNA have modulatory effect on ROS/NO production by PMjs from normal and tumor-bearing animals.